RANCANG BANGUN DAN PENGUJIAN KAMAR PENGERING INFRAMERAH UNTUK PENGERINGAN SINGKONG (Design, Construction, and Test of Infrared Dryer Room for Drying Cassava) - Haryanto, Aidil; Novrinaldi, Novrinaldi; Putra, Satya Andika (Baristand Industri Banda Aceh, 2016)
A model of infrared dryer for drying post-harvest products was designed and tested. Infrareddryer is one of an alternative food tool which mostly used when the production process occur for dryingpost-harvest products to increase time efficiency and product quality. Infrared drying technology has highefficiency because its radiation go through inside area of molecule item without hot air mediator like theone in convection and conduction process. This tool is designed with 2 x 2 x 2 m of outer dimension whichhas one exhaust fan, two fans, two air holes, two shelves, one infrared dryer (gasolec), and one control tool.Drying capacity is about 36 kg/batch. In a test, dryed products were sliced cassava with thickness between1-2 mm as many of 12 kg/3 hour with 50 oC dan 60 oC temperature. The data were taken at four point insidedryer. At 50 oC drying temperature the moisture content of cassava were 12,28% at T1, 14,93 % at T2,18,70% at T3 and 20,62% at T4 while at 60 oC drying temperature, the moisture content of cassava were7,36% at T1, 14,57 % at T2, 11,30% at T3, and 17,05% at T4 with average elpiji consumption is1,5 kg/batch. RH value were stable between 40-50 %.